Detection of six potato viruses using double antibody sandwich ELISA from in vitro, screen house and field grown potato crops in Ethiopia - Tessema, L.; Kakuhenzire, R.; Seid, E.; Tafesse, S.; Tadesse, Y.; Negash, K.; McEwan, M. (Springer, 2024)
Virus infection in seed potato reduces yield, and the problem is exacerbated when an early-generation seed is affected. The prevalence of six key potato viruses, PVY, PVX, PLRV, PVA, PVS, and PVM, was assessed among decentralized seed multipliers such as individuals, farmer seed group cooperatives, private companies, and agricultural research centers that produce early generation seed in six major potato growing districts in Ethiopia. A total of 262 leaf samples were randomly collected from potato plants and analyzed using a double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) for six major potato viruses. Potato virus prevalence was calculated as the proportion of samples that tested positive for the viruses against the total number of samples tested. The prevalence of infection with at least one of the six viruses was 98.2%. Among the samples analyzed, 17.2% had a single viral infection with one of the six viruses while the majority had multiple infections. The ELISA tests confirmed presence of latent virus infection in early generation seeds from the three EGS producers and in different seed classes. This result indicates that virus infection is widespread in the country, limiting potato production. To address this issue, it is critical to develop a robust system that prevents viral infection build-up and spread in the seed system through regular seed quality assurance and certification, particularly for early generation seed.